2001
DOI: 10.1291/hypres.24.25
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Night Shift Work on Psychologic State and Cardiovascular and Neuroendocrine Responses in Healthy Nurses.

Abstract: Night shift work has often been associated with increasing degree and frequency of various psychologic complaints. The study examined whether psychologic states after night work are related to adaptive alterations of the cardiovascular and neuroendocrine systems. We studied 18 healthy nurses (age 29+/-2 years) engaged in a modified rapid shift rotation system (day work, 8:15-17:15; evening work, 16:00-22:00; night work, 21:30-8:30). Blood pressure, heart rate, RR interval variability (L/H and HF power spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
3
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 12 publications
5
61
3
10
Order By: Relevance
“…Whereas there is evidence to suggest that shift work is associated with an increasing degree and frequency of psychological complaints [22,23,24], this study found no significant association between shift work and psychological problems. Regression analysis indicated that weekly working hours, type of employment and job unit were the only retained factors in the model.…”
Section: Discussioncontrasting
confidence: 95%
“…Whereas there is evidence to suggest that shift work is associated with an increasing degree and frequency of psychological complaints [22,23,24], this study found no significant association between shift work and psychological problems. Regression analysis indicated that weekly working hours, type of employment and job unit were the only retained factors in the model.…”
Section: Discussioncontrasting
confidence: 95%
“…A lot of research have shown the correlation between depression and shifts, especially night shifts (6,22,23). As shown by Ruggiero et al, night shifts can develop or even exacerbate sleep disorder, and on the other hand, there is a relationship between sleep disorder, affective disorder, and depression (23), so a direct relation exists between increased working hours and depression, which is consistent with our findings (24,25).…”
Section: Discussionsupporting
confidence: 90%
“…However, few studies have investigated the influence of long-term (or extended) shift work on the HPA axis and the awakening cortisol. Also, the findings from previous studies on the association between shiftwork and awakening cortisol have been inconsistent [19][20][21][22][23][24][25][26][27][28] ; both, high and low waking cortisol levels have been reported among shift workers.…”
Section: ©2012 National Institute Of Occupational Safety and Healthmentioning
confidence: 95%